Bioactive La(III), Er(III), Yb(III), Ru(III), and Ta(V) complexes of new organometallic Schiff base: Preparation, structural characterization, antibacterial, anticancer activities, and MOE studies. (10th April 2022) - Deghadi, Reem G.; Mohamed, Gehad G.; Mahmoud, Nessma F.
Abstract: Bioactive complexes [La(L)(H2 O)3 Cl]Cl2 .2H2 O (1 ), [Er(L)(H2 O)3 Cl]Cl2 (2 ), [Yb(L)(H2 O)2 Cl2 ]Cl.4H2 O (3 ), [Ru(L)(H2 O)2 Cl2 ]Cl.H2 O (4), and [Ta(L)(H2 O)Cl5 ] (5 ) have been prepared from 2‐acetylferrocene derivative Schiff base (L ) and characterized with different spectroscopic tools. Infrared (IR) spectral data proved the action of the ligand as a neutral bidentate Schiff base, coordinating via N‐azomethine and N‐pyrazole. Ta(V)‐complex was eight‐coordinated complex, whereas others were six‐coordinated complexes. Molar conductance results showed that La(III) and Er(III) chelates were 1:2 electrolytes, Yb(III) and Ru(III) chelates were 1:1 electrolytes, and Ta(V) chelate was non‐electrolyte. Thermal behavior of all compounds was characterized by thermogravimetric analysis/differential thermogravimetric analysis (TG/DTG) curves with mass loss related to dehydration, coordination, and decomposition steps. Growth inhibitory effect and IC50 values of compounds toward MCF‐7 cancer cell line were measured, and the data revealed that all complexes showed higher anticancer activity than free ligand. The lowest IC50 value was 4.5 μg/mL for La(III) and Ru(III) complexes. Furthermore, almost complexes showed good activities against Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, and Staphylococcus aureus species with inhibition zone diameter in the range of 10–15 mm/mg. While, they had no antifungal activities against Candida albicans and Aspergillus flavas species. Finally, the strong binding affinity of ligand and its complexes with different protein receptors was confirmed by MOE studies. Abstract : Preparation and characterization of new ferrocenyl La(III)/Er(III)/Yb(III)/Ru(III)/Ta(V) complexes using different tools. Investigation of their antibacterial, antifungal, and anticancer activities. Theoretical studies of the strong binding affinity of ligand and its complexes with different protein receptors by MOE studies.